COMMUNITY EMPOWERMENT IN WASTE MANAGEMENT THROUGH THE "PATUH MUAMALAT" WASTE BANK PROGRAM IN LARANGAN VILLAGE, CANDI DISTRICT - Rohmah , Pramudita Aurelia Sivaur; Sukmana , Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to describe and analyze community empowerment in waste management through the waste bank program in Larangan Village. Method: The research employs a qualitative approach with data collected through interviews, observations, and field documentation, while data analysis follows the Miles and Huberman (1984) model, consisting of data collection, data reduction, data presentation, and conclusion drawing. Results: The findings indicate that community empowerment in Larangan Village has been achieved through three main aspects: (1) awareness empowerment, which has increased residents’ awareness and active participation in waste management through socialization and training; (2) capacity empowerment, where communities receive training and counseling to enhance knowledge and skills, supported by the establishment of waste management groups to strengthen organizational capacity; and (3) authority empowerment, which provides opportunities, authority, and competencies for communities to sustainably and independently manage waste. Novelty: This study contributes by offering an evaluative perspective on waste bank programs as a model of community-based empowerment that integrates awareness, capacity building, and authority, positioning waste management not only as an environmental initiative but also as a strategy for sustainable village development.